Growth and carcass development of Kedu x Arab cross under two feeding regimes - Iskandar, Sofjan (Indonesian Journal of Animal and Veterinary Sciences, 2005)
One hundred unsexed chicks of each group of Kedu x Arab cross, of Arab x Arab and of Kedu x Kedu were kept under intensive husbandry for about 52 days (from 32 to 84 days of age). Each group was allocated to 10 cages of 10 unsexed birds. Experimental rations consisted of main ingredients of ground yellow corn, soybean meal, rice bran and fishmeal. Experimental ration were R1 containing energy of 2920 kkal ME/kg with crude protein of 15.17%. R2a contained energy of 3087 kkal ME/kg with crude protein of 7.36% and R2b contained energy of 2336 kkal ME/kg with crude protein of 42,51%. R1 ration was given ad libitum for 24 hours and R2a ration was given from 08.00 a.m.â12.00 p.m. and continued with R2b ration was given up to 8.00 a.m. in the following day. Results showed that live bodyweight and bodyweight gain were not significantly different among the three groups of chicken. Feed consumption of Kedu x Arab cross was significantly lower than that of Kedu x Kedu nor Arab x Arab. Feed conversion ratio of Kedu x Arab cross was also significantly lower (3.74) than its comparative groups. Birds on R1 ration grew faster (804 g/bird) than that on R2a-R2b ration (738 g/bird) with feed consumption of 2135 g bird-1 52 day-1 on R1 ration versus 2338 g bird-1 52 day-1 on R2a-R2b ration. FCR of the birds were lower on R1 ration (3.44) than on R2a-R2b ration (4.26). Energy consumption, protein consumption, protein efficiency ratio, energy efficiency ratio did not show significant different among the three groups of chicken, but for all those variables under R1 ration were significantly higher than for those under R2a-R2b ration. Whole carcass and carcass cuts were not significantly affected by neither the kind of chickens nor dietary treatments. Development of liver was the slowest among development of other carcass cuts and organs, whilst development of breast meat was 4.4â6.0 times, and drumstick meat was 4.6â6.6 times. Â  Â  Key Words: Kedu x Arab Cross Chicken, Growth, Carcass